Klasifikasi Lirik Lagu Bertema Lingkungan dengan Metode Naive Bayes - Ardika, Putu Ode Irfan; Cahyadi Putra, I Gusti Ngurah Anom (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 4 (2023): JNATIA Vol. 1, No. 4, Agustus 2023, 2023)
Awareness of the importance of protecting the environment is becoming increasingly important in this modern era. Humans as inhabitants of the earth have a responsibility to protect and maintain the  natural environment,they  live  in.  Songs  can  be  one  of  theimportant  roles  that  can  help awaken people to start protecting the environment they live in. This research makes it easy to find songs that have the theme of protecting the environment by classifying song lyrics. This research will  create  a  system  that  can  classify  environment-themed  song  lyrics  using  the  Naive  Bayes method with a Multinomial model. The results of the Naïve Bayes test with the Multinomial model get the best results on the composition of the training data and test data of 10.90 which produces a recall score of 38%, precision of 90.4%, F1 score of 53.5%, while for accuracy it gets the best score on the composition of 90:10 with a yield of 75%.